Understanding Portosystemic Collateral Anatomy - McBride, Aaron; Wallace, Alex; Patel, Indravadan; Ozen, Merve (Seminars in Interventional Radiology, 2025)
Portosystemic collateral pathways are a significant concern in interventional radiology, frequently manifesting in patients with cirrhosis or portal vein thrombosis. These pathways can lead to severe clinical complications, including gastrointestinal bleeding, hepatic encephalopathy, and liver failure. A thorough understanding of the anatomy, hemodynamic alterations, and clinical implications of these shunts is crucial for interventional radiologists to provide effective treatment while minimizing risks. This article reviews the clinical presentations associated with portosystemic shunts, explores the anatomical variants and altered flow dynamics, and discusses the latest endovascular treatment strategies to optimize patient outcomes.
Keywords: interventional radiology; anatomy; portal vein; collateral; portosystemic